Multiple presence and heterogeneous distribution of HIV-I subtypes in Nigeria (2001)
Human immunodefiency virus types I(HIV) subtypes circulating in Nigeria was determined by using the Peptide based Enzymes Immuno-Assay (PELISA) to anlayze sera or plasma samples collected from 925 individuals in southeastern and nothern) of Nigeria. The synthetic peptides used as the capture antigens in the PELISA were design from the consensus sequence of the thrid hypervariable region. (V3 loop) of HIV-I subtypes A, B, C, D, E and O of HIV-I. The assay was initially validated using plasma samples from individuals infected with various genetically identified HIV-I subtypes in Europe and AFrica. Any serum or plasma samples that reacted with more than one peptide was re-tested using the same antigen panel in a limiting ELISA technique. The result co- circulation of multiple HIV-I subtypes including A, B, C, D, E and O in Nigeria. Varying prevalence of specific antibodies to the six HIV-I subtypes included in the PELISA panel were detected among infected individuals (74), B=2.5%(23) and group O, 2.4%(20). Thirty-six (3.9%) of the samples from the northen and southeastern regions reacted with HIV-I subtype O and B peptides respectively. As far as it can be ascertained, this is the first report of dtection of HIV-I subtypes B, D, and E in Nigeria. Furthermore, the result of this work indicated widespread circulation of multiple HIV-I subtypes in Nigeria. Therefore a polyvalent vaccine will be the best option for effective prophylactic immunization against HIV-I infection in Nigeria.